MEDIA PEMBELAJARAN INTERAKTIF PENGENALA REPRODUKSI PADA HEWAN DAN TUMBUHAN BERBASIS MULTIMEDIA - Achmad Fauzi (Jurnal Informatika Kaputama (JIK), 2019)
In the world of today's education teacher educators and parents who give a lot of information about the reproduction of animals and plants is to deliver orally. In this way children sometimes difficult to grasp the meaning of what is being said by the teacher because it was considered less attractive.There are still many schools are only concerned with cognitive aspects and less looked at the issue of student motivation. It also occurs on the level of Elementary School (SD), especially on the subjects of science (IPA) on the reproduction of animals and plants. Background of the authors formulate the lack of interactive media is used to introduce to the students about how animals and plants reproduce. Lessons in SD Taman Siswa still conventional.            In this research, problem definition to be more focused and detailed. The results of this interactive learning is the author can facilitate students in the learning process or method of reproduction of the breeding of animals and plants are more communicative by using Adobe Flash CS6 software.